Monitoring the change in the value of the apparent viscosity of emulsion systems with different wax concentrations - Katona, Gabor; Kalić, Marina; Vojvodić, Slađana; Babić, Marina; Hadnadjev, Miroslav (Archives of Pharmacy, 2022)
Disperse systems play an important role in pharmacy. Physico-chemical properties of these systems greatly affect the release properties and distribution of active substances on the skin. In addition to consistency and density, waxes can also change the occlusive-emollient properties of the preparation. The aim of the study is to monitor the change in the value of the apparent viscosity of emulsion systems with different concentrations of cetyl palmitate. Ten preparations of identical composition were made, with different wax content (2,5-25%). The aqueous phase (sodium polyacrylate, glycerol, polysorbate 20, phenoxyethanol, lactic acid, water) was added to the oil phase (cetyl palmitate, caprylic triglycerides, cetyl diglyceryl trimeticone, tocopheryl acetate) and the preparation was homogenized with a laboratory stirrer (HS-D Overhead Stirrer, Witeg Laboretechnik) for 7 minutes, at 1200 rpm. Rheological tests were determined on a Haake MARS (Thermo Scientific, Karlsrue, Germany) using a measuring instrument of a Z20 DIN cylinder at a temperature of 22±0,1°C. Flow curves were examined using the hysteresis procedure. Based on the obtained results, the values ​​of apparent viscosities were gathered at the maximum shear rate of 50 s-1. As the wax content increased, the viscosity increased to a wax concentration of 22.5%. It is assumed that under the given conditions, the decrease in the value of apparent viscosity in wax concentrations higher than 22.5% is a consequence of the destabilization of emulsions caused by the crystallization of cetyl palmitate.